IMF Survey, Volume 31, Issue 22. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2002)
IMF economists and researchers from outside the institution gathered at the IMF's Third Annual Research Conference on November 7-8. The conference had an overarching theme of capital flows and global governance but also dealt with an eclectic array of other issues that economists at the IMF and elsewhere are exploring.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet